2020
DOI: 10.1177/0960327120969968
|View full text |Cite
|
Sign up to set email alerts
|

Induction of apoptosis in indole-3-carbinol-treated lung cancer H1299 cells via ROS level elevation

Abstract: This study was focused on investigating the anticancer potential of indole-3-carbinol (I3C) against lung cancer H1299 cells via an increase in ROS levels. To investigate the induction of growth arrest and/or cell death in H1299 cells, a cell cycle arrest assay, terminal deoxynucleotidyl transferase (TdT)-mediated dUTP-biotin nick-end labeling (TUNEL) assay, and reactive oxygen species (ROS) detection assay were performed. Through the TUNEL assay, we detected I3C-induced DNA fragmentation. Fluorescence-activate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 62 publications
1
10
0
Order By: Relevance
“…Previous studies represented to present that overexpression of HGF/cMet inhibited apoptosis in cancer cells via modulating mitochondrial proteins [40]. ROS-mediated apoptosis is critically associated with the intracellular ROS accumulation and regulation of the proapoptotic BH3-only proteins (Bim and Bax) and anti-apoptotic proteins (Bcl-xL) expression, which triggers mitochondrial membrane permeabilization [41,42]. Thus, we verified that transfection of Crispr-HGF and H2O2 induced apoptosis in HCC Huh7 and Hep3B cells.…”
Section: Discussionsupporting
confidence: 69%
“…Previous studies represented to present that overexpression of HGF/cMet inhibited apoptosis in cancer cells via modulating mitochondrial proteins [40]. ROS-mediated apoptosis is critically associated with the intracellular ROS accumulation and regulation of the proapoptotic BH3-only proteins (Bim and Bax) and anti-apoptotic proteins (Bcl-xL) expression, which triggers mitochondrial membrane permeabilization [41,42]. Thus, we verified that transfection of Crispr-HGF and H2O2 induced apoptosis in HCC Huh7 and Hep3B cells.…”
Section: Discussionsupporting
confidence: 69%
“…Primary antibodies were diluted to 1 : 500~1000 ratio, and secondary antibodies were diluted to 1 : 5000 ratio for use. All the experimental protocols were referred from our previous publications [ 13 , 45 , 46 ].…”
Section: Methodsmentioning
confidence: 99%
“…The results show that compound 16 h-treated could activate mitochondria-associated apoptotic pathway to induce apoptosis and suppress the proliferation of MGC803 cells in a dose-dependent manner, which can be proved by the increase in Bax and cleaved caspase-3/7/9 as well as the decrease in Bcl-2 [ 83 ]. Another simple indole alkaloid, indole-3-carbinol (I3C), a naturally occurring compound derived from multiple cruciferous vegetables, including cabbage, cauliflower, and radishes, contributes to inducing cancer cell growth arrest and exerts an anti-proliferative effect [ 84 ]. The previous experiment has shown that I3C-treated can induce increased expression of ROS in lung cancer H1299 cells, thereby activating the apoptosis-related signaling cascades, accompanied by the increased expression of pro-apoptotic proteins forkhead box O 3 (FOXO3), Bax, and Bim and the decreased expression of anti-apoptotic proteins Bcl-2 and Bcl-xL [ 84 ].…”
Section: Targeting Apoptotic Signaling Pathways With Indole Alkaloids...mentioning
confidence: 99%
“…The results show that compound 16 h-treated could activate mitochondria-associated apoptotic pathway to induce apoptosis and suppress the proliferation of MGC803 cells in a dose-dependent manner, which can be proved by the increase in Bax and cleaved caspase-3/7/9 as well as the decrease in Bcl-2 [83]. Another simple indole alkaloid, indole-3-carbinol (I3C), a naturally occurring compound derived from multiple cruciferous vegetables, including cabbage, cauliflower, and radishes, contributes to inducing cancer cell growth arrest and exerts an anti-proliferative effect [84]. The previous experiment has shown that I3C-treated can induce increased expression of ROS in lung cancer H1299 cells, thereby activating the apoptosis-related signaling cascades, accompanied by the increased expression of proapoptotic proteins forkhead box O 3 (FOXO3), Bax, and Bim and the decreased expression of anti-apoptotic proteins Bcl-2 and Bcl-xL [84].…”
Section: Targeting Bcl-2 Family and Cyt-cmentioning
confidence: 99%